2015
DOI: 10.5125/jkaoms.2015.41.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between mandibular condyle and angle fractures and the presence of mandibular third molars

Abstract: ObjectivesWe retrospectively evaluated the impact of mandibular third molars on the occurrence of angle and condyle fractures.Materials and MethodsThis was a retrospective investigation using patient records and radiographs. The sample set consisted of 440 patients with mandibular fractures. Eruption space, depth and angulation of the third molar were measured.ResultsOf the 144 angle fracture patients, 130 patients had third molars and 14 patients did not. The ratio of angle fractures when a third molar was pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
13
2
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 29 publications
8
13
2
1
Order By: Relevance
“…Our results were statistically significant and complemented the study put forth by Mah et al, who also proved that class II position B was prevalent among angle fractures, while absence of third molar (class 0 position 0) and class I position A was one of the key reasons for condyle fractures to occur. 1 Iida et al supported the fact that class I was most responsible for mandibular fractures but unerupted third molars with class II position B and class III were accountable for the fractures to occur at the angle region, hence supporting our results for the same. 20 Safdar and Meechan put forth the hypothesis that the amount of bony space occupied by an unerupted third molar can establish a direct relationship between the relative loss of bony integrity and weakness of that area of bone.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Our results were statistically significant and complemented the study put forth by Mah et al, who also proved that class II position B was prevalent among angle fractures, while absence of third molar (class 0 position 0) and class I position A was one of the key reasons for condyle fractures to occur. 1 Iida et al supported the fact that class I was most responsible for mandibular fractures but unerupted third molars with class II position B and class III were accountable for the fractures to occur at the angle region, hence supporting our results for the same. 20 Safdar and Meechan put forth the hypothesis that the amount of bony space occupied by an unerupted third molar can establish a direct relationship between the relative loss of bony integrity and weakness of that area of bone.…”
Section: Discussionsupporting
confidence: 87%
“…29 However, Tevepaugh and Dodson failed to hypothesize the relationship between angle fracture and mandibular third molar. 1,8 Specifically, for condylar fractures, Duan and Zhang found class 0 to have a higher incidence followed by class I which supported our study; however, position C was more prominent as compared with position A, which contradicted our findings. 16 Wolujewicz et al also contradicted different studies stating that the presence of third molar does have an effect on the angle and condyle fractures, but the position is not a predisposing factor.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…2,10,12,13 The possible explanation for this relationship is that mandibular third molars weaken the mandible by decreasing the cross-section area of bone. 10,14,15 Krimmel et al 16 reported that mandibular angle region with an impacted third molar is an area of lowered resistance to external forces. This observation has also been confirmed by the experimental studies on monkey mandible.…”
Section: Discussionmentioning
confidence: 99%
“…Similar observation was made by Zhu et al 1 They found a relation between presence of unerupted mandibular third molar with incidence of condyle fracture and provided strong clinical evidence to suggest that the removal of unerupted mandibular third molar predisposes the mandible to condyle fracture. 13,14 This suggests that if the mandibular angle region is made more resistant to fracture under a traumatic force, such trauma would create a fracture elsewhere and specially in the mandibular condyle.…”
Section: Discussionmentioning
confidence: 99%